2020
DOI: 10.1002/jcp.29589
|View full text |Cite
|
Sign up to set email alerts
|

CircBACH1 (hsa_circ_0061395) promotes hepatocellular carcinoma growth by regulating p27 repression via HuR

Abstract: In recent years, an increasing number of circular RNAs (circRNAs) have been discovered in hepatocellular carcinoma (HCC). However, the functions of most circRNAs require further investigation. Here, we found that circBACH1 was significantly upregulated in HCC tissues and that high circBACH1 levels were closely associated with poor prognosis. In addition, circBACH1 could promote HCC growth by accelerating cell cycle progression in vitro and in vivo. We next investigated the cellular and molecular mechanisms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 47 publications
(32 reference statements)
2
57
0
Order By: Relevance
“…For instance, HuR has been reported to promote the progression of many cancers by enhancing the expression of multiple angiogenic factors [29]. Recent studies revealed that circRNAs may impair the stabilization and translation of mRNAs by competitively binding with HuR [30,31]. Consistently, in the present study, we proved that circDLC1 could reduce the interaction between HuR and MMP1 mRNA, therefore inhibit the expression of MMP1 and HCC progression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, HuR has been reported to promote the progression of many cancers by enhancing the expression of multiple angiogenic factors [29]. Recent studies revealed that circRNAs may impair the stabilization and translation of mRNAs by competitively binding with HuR [30,31]. Consistently, in the present study, we proved that circDLC1 could reduce the interaction between HuR and MMP1 mRNA, therefore inhibit the expression of MMP1 and HCC progression.…”
Section: Discussionsupporting
confidence: 89%
“…HuR is the omnipresent member of the Hu/ELAV (human/embryonic lethal abnormal vision) RBP family and is responsible for the stabilization and (or) translation of many target mRNAs, which typically bear Urich 3 UTRs (27)(28)(29). Importantly, previous reports demonstrated that circRNA may impair the stabilization and translation of mRNAs by competitively binding with RNA-binding protein HuR (30,31). Thus, we hypothesized that circDLC1 may act as "sponges" for HuR, leading to decreased expressions of downstream target mRNA and protein.…”
Section: Circdlc1 Inhibited the Expression Of Mmp1 By Reducing The Inmentioning
confidence: 92%
“…Total RNA was extracted using TRIzol reagent (#15596-026, Invitrogen), nuclear and cytoplasmic RNA was extracted with the PARIS™ Kit (#AM1921, Thermo Fisher) as previously reported [13]. RT-qPCR kits were purchased from TaKaRa Bio Inc (Dalian, China) and cDNA was synthesized according to the manufacturer's instruction.…”
Section: Quantitative Reverse-transcription Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Recently, numerous circRNAs have found to be dysregulated in HCC. For example, CircBACH1 (hsa_circ_0061395) is signi cantly upregulated in HCC tissue and circBACH1 knockdown suppresses the proliferation and increased apoptosis of HCC cells by regulating p27 repression via HuR [13]. CircASAP1 acts as a ceRNA for miR-326 and miR-532-5p to mediates tumor-associated-macrophage (TAM) in ltration [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous circRNAs have found to be dysregulated in HCC. For example, CircBACH1 (hsa_circ_0061395) is signi cantly upregulated in HCC tissue andcircBACH1 knockdown suppresses the proliferation and increased apoptosis of HCC cells by regulating p27 repression via HuR [8]. CircASAP1 acts as a ceRNA for miR-326 and miR-532-5p to mediates tumor-associated-macrophage (TAM) in ltration [9].…”
Section: Introductionmentioning
confidence: 99%